Humanitarian Contraindications: A Case Study of Refugees Confused between the United States and Mexico - WARD, Mourad; ZAAMOUCHE, Fouzia (Journal of Human Sciences, 2020)
This world is full of internal, or international conflicts, which are the subject of many damage and grave violations of humanity, which leads people to search for a place of security to provide a way of life. But these conflicts are not the only ones that push people to search for ways of life. Within the systems of some countries that cause inequality of rights among citizens, it also motivates them to find a better place to obtain their rights, the first of which is the right to life. Among these are refugees from South American countries who are going to the United States, Seekers who remain trapped between the borders of the United States of America and Mexico, which will review it in our research on the problem of these refugees with the approval of the refugee protection and protection of the 1951 Convention states.